The “Souths” of the “Wests”. Southern critique and comparative housing studies in Southern Europe and USA - Tulumello, Simone (2021)
Southern urban critique has enriched our understanding of global uneven development, but often ended up constructing a dichotomous understanding of two apparently homogeneous fields: the Global North (or West) and South. This has been particularly evident in housing studies. In this article, I advocate for a relational, multi-scalar and comparative approach to southern urban critique, capable of exposing quasi-colonial relations within the urban “West”; and apply it to the exploration of housing dynamics and systems in Southern Europe and Southern USA—two regions linked to their continental “cores” by historical patterns of uneven and combined development. Despite being characterized by different urban frameworks and housing systems, these regions have in common analogous patterns of globalization and neoliberalization, with similar impacts over housing, especially in the aftermaths of the global economic crisis. By discussing how global trends intersect with regional contexts, I aim to provide conceptual and epistemological instruments for deepening the analytical grasp and political relevance of southern (urban) critique.